Influência de polimorfismos nos genes FcγRIIa, CD209, VDR, TNF-α, IL-4, IL-6 e INF-γ na persistência de sintomas clínicos da dengue na fase de covalescença - Dettogni, Raquel Spinassé (2015)
Differences in host susceptibility to infection, in the severity and permanence of the clinical picture of disease can be attributed, in part, to variations in the immune response. These variations are associated with single nucleotide polymorphisms (SNPs). As a previous study, the characterization of the general population of the Espírito Santo (ES)-Brazil and of a subpopulation of the state, of pomeranian origin, was performed as the SNPs -131 H/R, -336 A/G, TaqI, -308 A/G, -590 T/C, -174 G/C and +874 A/T in FcγRIIa, CD209, VDR, TNF-α, IL-4, IL-6 and IFN-γ genes, respectively. One hundred individuals of the Grande Vitória represented the general population of ES and 59 individuals of Santa Maria de Jetibá represented the population of Pomeranian origin. As the acute phase of dengue is well characterized, this study aimed to expand the knowledge of the phase of convalescence. Ninety-six individuals diagnosed with symptomatic dengue in late 2012 and early 2013, in ES, were followed for 60 days from the onset of symptoms by completing a clinical and epidemiological questionnaire in four interviews. The persistence of 37 clinical symptoms of dengue was assessed. To analyze the influence of the genetics of the host immune system in the persistence of clinical symptoms of dengue in the convalescent phase, the association between seven SNPs, for which the population of ES was characterized, and the persistence of symptoms was determined. Genomic DNA of study participants was extracted from peripheral blood and genotyping of SNPs was performed by polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP). The genotype frequencies of all SNPs were found in Hardy-Weinberg equilibrium (HWE), except for the SNP in the IL-6 gene. There was no statistically significant difference in genotype frequencies of SNPs in FcγRIIa, CD209, VDR, TNF-α and IL-4 genes between the two populations. A statistically significant difference was found between the two populations in the genotypic distributions of SNPs in IL-6 (p = 0.03) and INF-γ (p = 0.007) genes. Thirty and sixty days after the onset of symptoms, 38.5% and 11.5% of symptomatic patients with dengue reported having at least one clinical symptom of dengue, respectively. Symptoms among, the most persistent were related to fatigue syndrome as myalgia, arthralgia, asthenia and malaise, myalgia being the most frequent. The persistence of symptoms at 30 days was associated with female gender (p = 0.044) and persistent constitutional symptoms was associated with secondary dengue (p = 0.041). FcγRIIa gene SNP, was associated with persistent symptoms at 30 days in the subgroup of patients with secondary dengue (p = 0.046), and presence of the H allele was associated with non-persistence of symptoms (p = 0.014). The presence of the A allele in the TNF-α gene SNP was associated with non-persistence of symptoms in the subgroup of patients with secondary dengue (p = 0.025), with the GG genotype associated with persistent neurological, psychological and behavioral symptoms in 30 days (p = 0.038). The presence of the C allele in the IL-6 gene SNP was associated with persistent dermatological symptoms at 30 days (p = 0.005). Genetic profiling of these SNPs may favor the establishment of immunogenetic markers associated with the convalescent infection phase by the dengue virus (DENV).